A territorial perspective on urban and regional energy transitions: Shifting Power Densities in the Berlin-Brandenburg Region - Benedikt Walker (International Journal of Urban and Regional Research, 2022)
The interdependent development of subnational territories and energy transitions deserves greater attention. Territories demarcate spheres of influence, order relations of energy supply and demand, and offer opportunities and restrictions for local energy autonomy. Nevertheless, territorial perspectives on urban and regional energy transitions are conceptually underdeveloped. Drawing from political geography, this article presents a conceptual framework for understanding how subnational territories shape energy transitions and vice versa. This territorial perspective offers critical insights for research into the (urban) materiality of renewables, energy landscapes and uneven development. First, many cities will rely on renewable energy supply from rural territories to become carbon neutral, due to the low power densities of renewables. Second, governance actors mobilize territorial practices to create and disrupt relations between different energy landscapes. Finally, territorial boundaries are resources in governance processes and structuring elements of uneven development. I use the framework to analyze a case study of a wind energy conflict in three municipalities next to Berlin, which illustrates how Berlin's government asserts its territorial priorities and creates renewable energy hinterlands in a process I conceptualize as hinterlandization.
Keywords: 300; wind turbines; territory; hinterlandization; urbanization; spatial planning; governance; uneven development; energy landscape; sprawl; segregation; Berlin-Brandenburg; Germany